2015
DOI: 10.1080/21645515.2015.1078042
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus vaccination in general practice in France, three years after the implementation of a targeted vaccine recommendation based on age and sexual history

Abstract: In France, vaccination against human papilloma virus (HPV) was recommended in 2007 for all 14-year-old girls as well as "catch-up" vaccination for girls between 15-23 y of age either before or within one year of becoming sexually active. We evaluated the vaccine coverage according to the eligibility for vaccination in a sample of young girls aged 14 to 23 years, who were seen in general practices. A survey was proposed to 706 general practitioners (GPs) and carried out from July to September 2010. GPs, also ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(17 citation statements)
references
References 21 publications
0
15
0
2
Order By: Relevance
“…Among the 25 studies identified for this review ( Agrinier et al, 2017 ; Barjhoux and Glatigny, 2009 ; Bouvret et al, 2016 ; Casimont, 2015 ; Chauvet, 2016 ; Collange et al, 2016 ; Degoue, 2019 ; Erpeldinger et al, 2012 ; Gougenheim-Fretin, 2014 ; Houdjal, 2017 ; Killian et al, 2016 ; Lamirand, 2015 ; Lasset et al, 2014 ; Leicht, 2016 ; Lutringer-Magnin et al, 2011 ; Manolitsi, 2012 ; Martinez et al, 2016 ; Pelissier and Bastides, 2008 ; Piana et al, 2009 ; Plessis et al, 2012 ; Raude et al, 2016 ; Sadki, 2016 ; Thierry et al, 2016 ; Tutala, 2019 ; Verger et al, 2015 ), 18 reported quantitative and seven qualitative designs ( Table 1 ). The majority of the studies were conducted either before 2011 ( Barjhoux and Glatigny, 2009 ; Erpeldinger et al, 2012 ; Lasset et al, 2014 ; Lutringer-Magnin et al, 2011 ; Pelissier and Bastides, 2008 ; Piana et al, 2009 ; Plessis et al, 2012 ; Thierry et al, 2016 ) with some around 2007–2008 i.e.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Among the 25 studies identified for this review ( Agrinier et al, 2017 ; Barjhoux and Glatigny, 2009 ; Bouvret et al, 2016 ; Casimont, 2015 ; Chauvet, 2016 ; Collange et al, 2016 ; Degoue, 2019 ; Erpeldinger et al, 2012 ; Gougenheim-Fretin, 2014 ; Houdjal, 2017 ; Killian et al, 2016 ; Lamirand, 2015 ; Lasset et al, 2014 ; Leicht, 2016 ; Lutringer-Magnin et al, 2011 ; Manolitsi, 2012 ; Martinez et al, 2016 ; Pelissier and Bastides, 2008 ; Piana et al, 2009 ; Plessis et al, 2012 ; Raude et al, 2016 ; Sadki, 2016 ; Thierry et al, 2016 ; Tutala, 2019 ; Verger et al, 2015 ), 18 reported quantitative and seven qualitative designs ( Table 1 ). The majority of the studies were conducted either before 2011 ( Barjhoux and Glatigny, 2009 ; Erpeldinger et al, 2012 ; Lasset et al, 2014 ; Lutringer-Magnin et al, 2011 ; Pelissier and Bastides, 2008 ; Piana et al, 2009 ; Plessis et al, 2012 ; Thierry et al, 2016 ) with some around 2007–2008 i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Among the 25 studies identified for this review ( Agrinier et al, 2017 ; Barjhoux and Glatigny, 2009 ; Bouvret et al, 2016 ; Casimont, 2015 ; Chauvet, 2016 ; Collange et al, 2016 ; Degoue, 2019 ; Erpeldinger et al, 2012 ; Gougenheim-Fretin, 2014 ; Houdjal, 2017 ; Killian et al, 2016 ; Lamirand, 2015 ; Lasset et al, 2014 ; Leicht, 2016 ; Lutringer-Magnin et al, 2011 ; Manolitsi, 2012 ; Martinez et al, 2016 ; Pelissier and Bastides, 2008 ; Piana et al, 2009 ; Plessis et al, 2012 ; Raude et al, 2016 ; Sadki, 2016 ; Thierry et al, 2016 ; Tutala, 2019 ; Verger et al, 2015 ), 18 reported quantitative and seven qualitative designs ( Table 1 ). The majority of the studies were conducted either before 2011 ( Barjhoux and Glatigny, 2009 ; Erpeldinger et al, 2012 ; Lasset et al, 2014 ; Lutringer-Magnin et al, 2011 ; Pelissier and Bastides, 2008 ; Piana et al, 2009 ; Plessis et al, 2012 ; Thierry et al, 2016 ) with some around 2007–2008 i.e. the period where HPV vaccination was implemented in France ( Barjhoux and Glatigny, 2009 ; Erpeldinger et al, 2012 ; Lutringer-Magnin et al, 2011 ; Pelissier and Bastides, 2008 ; Piana et al, 2009 ), or over the 2011–2015 period ( Agrinier et al, 2017 ; Bouvret et al, 2016 ; Casimont, 2015 ; Collange et al, 2016 ; Gougenheim-Fretin, 2014 ; Killian et al, 2016 ; Lamirand, 2015 ; Manolitsi, 2012 ; Martinez et al, 2016 ; Raude et al, 2016 ; Verger et al, 2...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To achieve high HPV vaccination coverage, a nationwide school-based vaccination programme should be considered for Germany to reach those children who have not visited a doctor between the ages of 9 and 14 years, who have not attended the J1 health check-up, or whose doctors have not yet recommended HPV vaccination. School vaccination programmes are most common in Anglo-Saxon and Nordic countries, where they normally lead to a vaccination coverage of >70%, as in Australia (2016: girls 79%, boys 73%; [120]), Canada (2013: girls 73%; [121] [127]). One exception is Denmark, which initially achieved vaccination coverage of >70% after introduction of the vaccination without a school vaccination programme [128].…”
Section: Implementation Of a General Hpv Vaccinationmentioning
confidence: 99%